Milyen „készen talált” kapcsolatokból épülnek fel a vállalkozáson belüli viszonyok? - Kuczi, Tibor (Szociológiai Szemle, 2024)
Over the past two to three years private companies have come into existence in Hungary at a faster rate than the leadership experience needed to make them work. The paper investigates which occupational illations in the new enterprises, their development from pre-existing connections, and how these previous relationships undergo change during the development of the companies. Several cases are described, among them the role played by the former (state-owned) workplace in the development of business contacts; the utilization of previous connections that have been established either through cooperation in the second economy or developed within the traditional neighbourhood and authority relationships of local communities or, finally, within the extended family.